Oral microbiota distinguishes patients with osteosarcoma from healthy controls - Chen, Yu; Li, Chao; Wang, Xin; Zhang, Chun Lei; Ren, Zhi Gang; Wang, Zhong Quan (Frontiers in Cellular and Infection Microbiology, 2024)
The human microbiota plays a key role in cancer diagnosis, pathogenesis, and treatment.However, osteosarcoma-associated oral microbiota alterations have not yet been unraveled. In this study, 147 oral samples were collected from participants, the oral microbiota in osteosarcoma was characterized and an osteosarcoma microbial classifier was constructed.Compared with healthy controls (n = 90), the microbial richness and diversity of the tongue coat were significantly increased in osteosarcoma patients (n = 45) and the microbial community could distinguish osteosarcoma from healthy controls. 14 genera including Rothia, Halomonas, Rhodococcus, and Granulicatella were remarkably reduced, whereas Alloprevotella, Prevotella, Selenomonas, and Campylobacter were enriched in osteosarcoma.Eventually, the optimal four operational taxonomy units were identified to construct a microbial classifier by the random forest model via a fivefold cross-validation, which achieved an area under the curve of 99.44% in the training group (30 osteosarcoma patients versus 60 healthy controls) and 87.33% in the test group (15 osteosarcoma patients versus 30 healthy controls), respectively. Notably, oral microbial markers validated strong diagnostic potential distinguishing osteosarcoma patients from healthy controls. Overall, this study comprehensively characterizes the oral microbiota in osteosarcoma and reveals the potential efficacy of oral microbiota-targeted biomarkers as a noninvasive biological diagnostic tool for osteosarcoma.